PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP KEMAMPUAN HOTS MATEMATIKA SISWA KELAS IV SD NEGERI 72 PALEMBANG - Rika Pebyola Simanjuntak; Misdalina; Ferri Hidayad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Think Pair Share (TPS) learning modelon the Higher Order Thinking Skills (HOTS) in mathematics of fourth-grade studentsat SD Negeri 72 Palembang. This research employed a quantitative method with atrue experimental design, specifically the Posttest-Only Control Group Design. Thepopulation consisted of all fourth-grade students, with a sample of 55 studentsselected using cluster random sampling, divided into an experimental class (27students) and a control class (28 students). Data were collected through a HOTS-based mathematics test consisting of essay questions. Prerequisite tests includednormality (Shapiro-Wilk) and homogeneity (Levene’s Test). The hypothesis wastested using an independent sample t-test. The results showed that the averagescore of the experimental class was 80.19, significantly higher than the control classwhich averaged 21.25. The t-test results indicated a significance value (2-tailed) of0.000 < 0.025, leading to the rejection of H0 and acceptance of Ha. Thus, it can beconcluded that the Think Pair Share learning model has a significant positive effecton the mathematical HOTS abilities of fourth-grade students at SD Negeri 72Palembang.